1990
DOI: 10.3354/meps061291
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and extracellular carbohydrates and lipids from marine bacteria during growth on soluble substrates and hydrocarbons

Abstract: The variability of extracellular excretions of 4 marine bacterial strains was investigated during growth on soluble (acetate or lactate) and insoluble (hydrocarbons) substrates. Cellular and extracellular protein, carbohydrate and lipid contents were estimated at the end of exponential growth phase. Emulsifying capacity of the cell-free culture medium was estimated. Lipid classes were characterized by using thin layer chromatography coupled with flame ionization detection. All strains were found to excrete org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…It has been suggested that excretion of metabolites is a pathway of energy dissipation that may contribute to the maintenance of intracellular stoichiometry (31a, 84). However, excretion of organic metabolites, including polysaccharides, lipids, proteins, and humiclike substances, has also been found under conditions of carbon and nutrient limitation in aquatic bacteria (48,63,67,146). Most excretion products are polymeric, and the biosynthesis of these substances typically exerts high energy requirements to the cell (117,133).…”
Section: Metabolite Excretionmentioning
confidence: 99%
“…It has been suggested that excretion of metabolites is a pathway of energy dissipation that may contribute to the maintenance of intracellular stoichiometry (31a, 84). However, excretion of organic metabolites, including polysaccharides, lipids, proteins, and humiclike substances, has also been found under conditions of carbon and nutrient limitation in aquatic bacteria (48,63,67,146). Most excretion products are polymeric, and the biosynthesis of these substances typically exerts high energy requirements to the cell (117,133).…”
Section: Metabolite Excretionmentioning
confidence: 99%
“…(60), Alcaligenes sp. PHY9, and Pseudomonas nautica strain 617 (24), and for the fungus Cladosporium resinae (61), the function of lipid export is unclear. As a part of surface-active compounds (also known as biosurfactants or bioemulsifiers), specialized lipids with a chemical structure different than those investigated in this study could play a role in the modification of medium properties and could therefore enhance the contact between bacteria and water-insoluble hydrocarbons.…”
Section: Discussionmentioning
confidence: 99%
“…The localization of neutral lipids in marine organisms is not restricted to the cell cytoplasm, as extracellular lipid deposition has been shown in studies with Alcaligenes sp. PHY9 and Pseudomonas nautica (24). The production of extracellular wax esters by Alcanivorax jadensis T9 growing on hexadecane was described a few years ago (11).…”
mentioning
confidence: 99%
“…Since bacterial growth required a direct contact of cells with a solube and/or non-soluble substrate, stimulation by using chemical or biological dispersant (emulsifier, surfactant) will increase degradation rate for many petroleum hydrocarbons compounds such as paraffin [8]; Polycyclic Aromatic Hydrocarbons [9]; crude oil [10,11]. Reference [12] showed high capacity of microbial adhesion to an hydrophobic substrates. We suggest some specific enzymes have been induced and released into liquid media system.…”
Section: Bioproduct (Metabolite By Product)mentioning
confidence: 99%